1993
DOI: 10.7326/0003-4819-119-9-199311010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death of a Carrier of X-Linked Emery-Dreifuss Muscular Dystrophy

Abstract: Emery-Dreifuss muscular dystrophy is associated with characteristic pathologic changes in the heart that can cause death in female carriers and affected men. Female carriers should be identified and evaluated because of the risk for sudden cardiac death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 0 publications
1
38
0
2
Order By: Relevance
“…The atria and ventricles are involved in heterogenic degeneration of the myocardium in which muscular tissue is replaced by fibrotic and adipose tissue [5,10,13]. In all patients except one leads were placed in areas with proper pacing parameters despite the possibility of local right ventricular degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The atria and ventricles are involved in heterogenic degeneration of the myocardium in which muscular tissue is replaced by fibrotic and adipose tissue [5,10,13]. In all patients except one leads were placed in areas with proper pacing parameters despite the possibility of local right ventricular degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of EDMD is exceptional because even mild pathology of the skeletal muscles is accompanied by cardiac pathology, which may result in sudden cardiac death (SCD) [5]. The first cardiologic symptoms are observed during the second to fourth decades of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of the pathologic processes at the atrial level is progressive and in a histopathologic post-mortem study on three hearts a marked loss of atrial myocardium was found, with evidence that the atrial myocardium had been replaced by adipose and fibrous tissue [28]. This impressive derangement of the atrial walls fits with the recent concepts of ‘atrial cardiomyopathy’[29], corresponding to any complex of structural, architectural, contractile or electrophysiological changes affecting the atria with the potential to produce clinically-relevant manifestations [30].…”
Section: Bradyarrhythmias Atrial Fibrillation and Atrial Fluttermentioning
confidence: 99%
“…Conduction disturbances may also involve the infranodal conduction system resulting in slow junctional escape rhythms or complete heart block. 6,7 Atrial standstill is a pathognomonic finding, 8 with a lack of atrial response to intracardiac electrical or mechanical stimulation. 9 Cardiomyopathy with poor left ventricular function occurs less commonly.…”
Section: Objectif : Présenter Le Cas D'un Patient Atteint De Dystropmentioning
confidence: 99%